Factores Competitivos De Éxito: Un Estudio De Las Pymes En El Estado De Hidalgo, México - Hernández, Blanca Cecilia Salazar; Moheno, Jessica Mendoza; García, María Dolores Martínez (European Scientific Journal, ESJ, 2018)
This paper focuses on the influence that small and medium-sized enterprises (SMEs) have on the economy in terms of generating employment and wealth. It also identified the problems that was derived from the limitations generated due to their size and the environmental aggressions in which they were developed. In this sense, the study of its characteristics in terms of strategy, performance, competitiveness, problems, and professionalization is of significant importance to its growth and permanence. To this end, this study aims to determine different strategic factors that SMEs must develop to ensure their competitiveness and performance. Based on a quantitative study of SME companies located in the state of Hidalgo, Mexico, some factors related to competitive performance were identified. Essentially, it was observed that SMEs of larger size and age, which are linked to other actors and that make use of strategic management tools as well as information and control systems, are competitively successful.